‘Lanna’ Local Wisdom in Promoting Well-being of Children: A Pilot Study - Chanprasit, Chawapornpan; Lirtmunlikaporn, Sumalee; Sethabouppha , Hunsa; jongrungrotsakul, waruntorn (Nursing Journal CMU, 2021)
Lanna local wisdom related to health is knowledge in caring population health focusing on health stability and placing value on holistic health. This pilot study was designed to explore Lanna local wisdom in caring for health promotion of children. Key informants, a total of 52, comprised tradition scholars, traditional healers, and caregivers of children, residing in Chiang Mai Province. Data collection was performed through focus group discussions and in-depth interviews. Data analysis was undertaken by content analysis The main results of the study illustrated that the spirit beliefs and all kinds of rituals of Lanna people were incorporated to child care for their well-being. Lanna people advanced their children’s readiness in physical, mental, social and spiritual aspects through socialization of family institute along with religion institute, adopting the ‘readiness’ concept and gradually building up children’s knowledge and essential skills for their living. This socialization aimed to enhance their children’s quality growth. Caring for child health promotion comprised caring for social-ethics, spiritual, physical, development, and intelligent. The study reflects that child care of Lanna people focused on the ‘quality’ of child development in all health aspects, which had integrated into daily living as habitual rites. Thorough understanding of local wisdom related to health among health professional is crucial for quality child care plan suitable to Lanna social and cultural context.